Alih Teknologi Pembuatan Lunas Baja Bagi Pengrajin Kapal Kayu Tradisonal di Kelurahan Galesong Kota, Kecamatan Galesong, Kabupaten Takalar - Ganding Sitepu; M.R. Firmansyah; Misliah -; W. Djafar; Rosmani -; Suandar Baso; Akbar Asis; A. Rahmat Darwis (Faculty of Engineering UNHAS, 2022)
South Sulawesi is known as a place for wooden shipbuilding. The main problem faced by craftsmen is the shortage of wood. The solution, proposed the use of steel as the keel of the ship. In collaboration with the wooden boat craftsman group